Default In And Credit Agreement And Implementation Of Solution Efforts (A Case Study Of Decision 336 / Pdt / G / 2016 / Pn.Smg) - Dhika Rachmat Pratama; Amin Purnawan (Jurnal Daulat Hukum, 2018)
To be implemented lending by banks, there must be an agreement between the banks as creditors and customers as debtors called credit agreement. In providing credit to the public, the Bank must be sure that the funds lent to the community it will be returned on time, with interest and with the terms that have been agreed between the bank and the customer that have been set forth in the credit agreement. In completing this study, the authors use a step to find data and collect data either through the study of literature and other data sources and to analyze the subject and object data obtained through sosiogis juridical approach, while sampling was conducted through interviews with directional type. This study focused on the integration or coherence in the manufacture / preparation of bank loan agreement and accommodate interests of the parties in a balanced manner in the bank credit agreement. The credit agreement that accommodates the interests of the parties in a balanced manner is expected to provide benefits and fairness to the parties that lead to the achievement of the objectives of law, the object of study in this research is related to the case of default on the decision number 336 / Pdt / G / 2016 / PN.SMGthat involving PT. Bank of Central Java as the plaintiff and Ir. Hj. Fatimah as a defendant.Keywords: Banks; Credit; Default